Inhibition of the Nav1.7 Channel in the Trigeminal Ganglion Relieves Pulpitis Inflammatory Pain - Kwon, Minjee; Jung, Il Young; Cha, Myeounghoon; Lee, Bae Hwan (Frontiers in Pharmacology, 2021)
Pulpitis causes significant changes in the peripheral nervous system, which induce hyperalgesia. However, the relationship between neuronal activity and Nav1.7 expression following pulpal noxious pain has not yet been investigated in the trigeminal ganglion (TG). The aim of our study was to verify whether experimentally induced pulpitis activates the expression of Nav1.7 peripherally and the neuronal activities of the TGs can be affected by Nav1.7 channel inhibition. Acute pulpitis was induced through allyl isothiocyanate (AITC) application to the rat maxillary molar tooth pulp. Three days after AITC application, abnormal pain behaviors were recorded, and the rats were euthanized to allow for immunohistochemical, optical imaging, and western blot analyses of the Nav1.7 expression in the TG. A significant increase in AITC-induced pain-like behaviors and histological evidence of pulpitis were observed. In addition, histological and western blot data showed that Nav1.7 expressions in the TGs were significantly higher in the AITC group than in the naive and saline group rats. Optical imaging showed that the AITC group showed higher neuronal activity after electrical stimulation of the TGs. Additionally, treatment of ProTxII, selective Nav1.7 blocker, on to the TGs in the AITC group effectively suppressed the hyperpolarized activity after electrical stimulation. These findings indicate that the inhibition of the Nav1.7 channel could modulate nociceptive signal processing in the TG following pulp inflammation.